The WADA code: the maximum extent of enforcement. Issue 2 (3rd April 2019) - Gandert, Daniel
ABSTRACT: This article describes how in addition to providing the minimum penalty for anti-doping violations, the World Anti-Doping Code provides the maximum penalty that may be provided. It explains how sports organizations, including the IOC, have repeatedly found that additional sanctions cannot be added for doping offences beyond the penalty prescribed by the code at the time of the athlete's offence.